(untitled) (Edad Media. Revista de Historia, 2018)
This study examines the development of the historiographic genre in the Papal States during the transition from the Middle Ages to the Renaissance. A typology of the sources is proposed according to chronology (universal, coetaneous and relating to antiquity), approach (annals, chronicles, urban diaries), and the specific aim (biography, stories, memoirs). In each case the historic and cultural context is studied, as well as the link between the author and the facts he relates, the literary characteristics and the content, and finally the possibilities and limitations that are offered to historical knowledge. Likewise, the technique and method used by the chroniclers are specified, especially in those cases where the chronicler acts as notary too. This study is not only limited to Rome but includes the regions of Lazio, Umbria and Marche in order to present a view that may lead to a comparative analysis between the works made in the papal city and those from the cities within pontifical jurisdiction.